Assessing the Feasibility of Developing in vivo Neuroprobes for Parallel Intracellular Recording and Stimulation: A Perspective - Spira, Micha E.; Erez, Hadas; Sharon, Aviv (Frontiers in Neuroscience, 2022)
Developing novel neuroprobes that enable parallel multisite, long-term intracellular recording and stimulation of neurons in freely behaving animals is a neuroscientist’s dream. When fulfilled, it is expected to significantly enhance brain research at fundamental mechanistic levels including that of subthreshold signaling and computations. Here we assess the feasibility of merging the advantages of in vitro vertical nanopillar technologies that support intracellular recordings with contemporary concepts of in vivo extracellular field potential recordings to generate the dream neuroprobes that read the entire electrophysiological signaling repertoire.